Analisis Determinan Yang Mempengaruhi Kepatuhan Wajib Pajak Bumi dan Bangunan Perdesaan dan Perkotaan di Kabupaten Dompu Dengan Kesadaran Wajib Pajak Sebagai Variabel Moderasi - Muh. Syahru Ramadhan; Samsudin; Rahmatul Laili (Jurnal Multidisiplin Madani, 2022)
This study aims to determine the various factors that can affect the compliance of rural and urban land and building taxpayers in Dompu district with taxpayer awareness as a moderating variable. Sampling using purposive sampling method. The type of data used in this research is primary data, which is collected through surveys. Respondents in this study were taxpayers who were in 4 sub-districts, namely taxpayers in Woja District, Pajo District, Hu'u District and Dompu District with a total of 100 respondents. The data analysis technique used multiple linear regression analysis using SPSS tools. This study found that taxpayer knowledge, tax sanctions affect the compliance of PBB-P2 taxpayers in Dompu Regency. Then the knowledge of taxpayers with awareness of taxpayers as a moderating variable affects taxpayer compliance with moderating variables of taxpayer awareness. Tax sanctions with taxpayer awareness as a moderating variable affect taxpayer compliance.